Comparison Of The Outcome Of Laparoscopic Vs Open Appendectomy in tertiary care hospital of Muzaffarabad - Naheed Akhtar, Farjad Shahid, Saman Naz, Raja Muhammad Ijaz,, Muhammad Asif, Muhammad Aamir Jameel, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the outcome of laparoscopic appendectomy in comparison to open appendectomy in patients admitted with acute appendicitis. Study design: Randomized controlled trial. Place and duration of study: Department of General Surgery, H.H SKBZ Hospital/ AK CMH Muzaffarabad from 23rd November 2019 to 22nd May 2020. Methodology: A total of 70 patients of age 15-60 years of either gender presenting with appendicitis were included. Patients with co-morbidities i.e. hypertension (BP≥140/90mmhg), diabetes (BSR>180mg/dl), liver (ALT>40IU, AST>40IU), anemia (Hb<10g/L) were excluded. In group A, open appendectomy was done. In group B, laparoscopic appendectomy was done. All surgeries were done under general anesthesia by a single surgical team with assistance of researcher. Duration of surgery was noted in minutes. After appendectomy, patients were detained in surgical ward and were observed there till discharge. Results: Mean operative time in Group A (open appendectomy) was 43.06±5.71 minutes while in Group B (laparoscopic appendectomy) was 50.71±3.67 minutes (p0.0001). Mean hospital stay in Group A (open appendectomy) was 4.0±0.73 days while in Group B (laparoscopic appendectomy) was 2.09±0.70 days (p0.0001). Wound infection in Group A (open appendectomy) was 8.57% while in Group B (laparoscopic appendectomy) was 2.86% (p0.303). Conclusion: This study concluded that outcome of laparoscopic appendectomy is better as compared to open appendectomy in patients presenting with appendicitis.